A discourse analysis of the generic structure of doctoral dissertation acknowledgments in a multicultural setting / Nurul Nadwa Ahmad Zaidi - Ahmad Zaidi, Nurul Nadwa (2014)
The existence of acknowledgment in academic paper has become an academic practice. This research takes the role to examine the differences in acknowledgements writing of doctoral dissertation among three major races in Malaysia. This paper explores the generic structure of doctoral dissertation acknowledgments of three major races in Malaysia through discourse analysis. The data was collected from several reliable online collection and libraries. The data collected for this study was using convenient sampling. The 50 samples from each race were selected based on their availability from local universities and universities abroad. The analysis of the findings includes the differences in moves used by the three major races in Malaysia which are Malay, Chinese and Indian. Qualitative and quantitative approaches were used in analysing the corpus of doctoral dissertation acknowledgements. The findings of the study disclosed that the structural arrangement of doctoral dissertation acknowledgements has the same structure with the arrangement proposed by Al-Ali (2006). There is no vast different of acknowledgement writing between the three races. From the findings, this study came out with a modified model of generic structure of doctoral dissertation acknowledgements. The study also reveals that the acknowledgement is a genre as it is used in communicative purpose. It is a normal practice embedded in academic culture of the community. It is proven that the practice conveys gratitude in academic writing. It is recommended that the future research can include the analysis of linguistic patterns in acknowledgement writing.